Green Tea Increases the Concentration of Total Mercury in the Blood of Rats following an Oral Fish Tissue Bolus. (2nd August 2015) - Janle, Elsa M.; Freiser, Helene; Manganais, Christopher; Chen, Tzu-Ying; Craig, Bruce A.; Santerre, Charles R.
Abstract : Fish has many health benefits but is also the most common source of methylmercury. The bioavailability of methylmercury in fish may be affected by other meal components. In this study, the effect of green tea on the bioavailability of methylmercury from an oral bolus of fish muscle tissue was studied in rats and compared to a water treated control group and a group treated with meso-2, 3-dimercaptosuccinic acid (DMSA), a compound used medically to chelate mercury. Rats were given a single oral dose of fish tissue via gavage and one of the treatments. Rats were given access to food for 3 h at 12 h intervals. They were dosed with each of the treatments with each meal. Blood samples were collected for 95 hours. Green tea significantly increased the concentration of total mercury in blood relative to the control, whereas DMSA significantly decreased it. In addition, feeding caused a slight increase in blood mercury for several meals following the initial dose.